Relasi Antagonistik Barat-Timur: Orientalisme vis a vis Oksidentalisme - Moh. Fudholi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2012)
The encounter of the East and the West due to such various interests as economic, political, scientific, cultural has been a major factor in the study of western scientists (Orientalists) about the East that produces a variety of works in the fields of archeology, history, literature, environment, customs, and Islamic studies. Meanwhile, resistance against Orientalism in the form of Occidentalism, as initiated by Hasan Hanafî, seems to be closely related to ‘obsession’ and hopes of someone who frustrated and dissatisfied with the condition of the world he has dealt with as the project of civilization he offered seemed to be too theoretical to be applied into the form of well-established science. This is a fact that, unlike Orientalism that has born from strength, power and has been then smoothly formed, Occidentalism was created by the East that was defeated and suffered from weakness and at the same time merely has an obsession. Despite the impression, apparently, what has been attempted in Occidentalism is dismantling the text, another interpretation, and building a new, more proportional context.